2016
DOI: 10.1016/j.hrthm.2015.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Infection and mortality after implantation of a subcutaneous ICD after transvenous ICD extraction

Abstract: The S-ICD is a suitable alternative for TV-ICD patients whose devices are explanted for any reason. Postimplantation risk of infection remains low even in patients whose devices were explanted for prior TV-ICD infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 31 publications
5
51
1
1
Order By: Relevance
“…[1][2][3][4] Thus, the S-ICD system has the potential to decrease periprocedural implantation risks, eliminate the problem of difficult venous access, reduce endovascular mechanical stress on leads, and decrease the risk of systemic device-related infection. [1][2][3][4][5] However, single case reports 6 and the IDE Study and EFFORTLESS Registry reported that the total complication rate was as high as 11%, with the majority being pocket infection, erosion, or discomfort. Nevertheless, this registry included the initial worldwide experience with the S-ICD, and implant complications rate are expected to decrease with increasing operator experience and better surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Thus, the S-ICD system has the potential to decrease periprocedural implantation risks, eliminate the problem of difficult venous access, reduce endovascular mechanical stress on leads, and decrease the risk of systemic device-related infection. [1][2][3][4][5] However, single case reports 6 and the IDE Study and EFFORTLESS Registry reported that the total complication rate was as high as 11%, with the majority being pocket infection, erosion, or discomfort. Nevertheless, this registry included the initial worldwide experience with the S-ICD, and implant complications rate are expected to decrease with increasing operator experience and better surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, particularly the superior parasternal incision is a potential source of skin erosion and infection. 2,4,5 Thus, a two-incision technique eliminating the superior parasternal incision has been developed. 7 This less invasive and simplified technique is safe and may help reducing complications in S-ICD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bridging patients with prior ICD therapies who require continuous ICD backup in the period between device explantation and reimplantation is particularly challenging . The options available to physicians include immobilization in an intensive care unit or telemetry ward, with continuous ECG monitoring where instant access to external defibrillation is provided; a wearable cardioverter‐defibrillator (WCD) ; and a subcutaneous ICD (S‐ICD) as a permanent reimplantation device …”
Section: Discussionmentioning
confidence: 99%
“…30 In patients who only need defibrillators and in whom no pacing is needed, the use of a subcutaneous implanted defibrillator should be considered as it reduces the risk of subsequent infection. 48 Subcutaneous ICD is effective in treating ventricular tachycardia and has been studied in many trials. 49 As a matter of fact, this type of device is associated with very low rates of infection, and if infection was to occur, the extraction of this device is much easier than the extraction of transvenous devices.…”
mentioning
confidence: 99%
“…49 Subcutaneous ICDs have been shown to have lower rates of infection even in patients in whom a previous transvenous CIED was explanted for infection. 48 In patients with high risk of infection, the use of epicardial leads can also be considered to reduce the risk of systemic infection. 30 Leadless pacemakers could also eventually be one of the options.…”
mentioning
confidence: 99%